2011
DOI: 10.1111/j.1365-2133.2011.10610.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining risk factors for developing systemic lupus erythematosus in patients with discoid lupus erythematosus

Abstract: Up to 28% of patients with discoid lupus erythematosus (DLE) are susceptible to developing systemic lupus erythematosus (SLE). To better characterize patients with DLE who have a higher potential of developing SLE, we reviewed studies contrasting, firstly, DLE-only patients (i.e. patients with DLE without SLE) and SLE patients with DLE (i.e. patients who are diagnosed with SLE and DLE simultaneously, and patients with SLE who later develop DLE), and secondly, DLE-only patients and patients with DLE who progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 28 publications
3
67
0
4
Order By: Relevance
“…DLE occurs more frequently in women in their fourth and fifth decade of life [11]. Patients with DLE generally have a more benign disease course as compared to patients with other CLE subtypes, with only a reported 5-10% developing SLE throughout their disease course [28,29]. Studies have shown that patients with generalized DLE are more likely to progress to systemic disease, compared to patients with localized DLE [9,30].…”
Section: How Can We Differentiate the Cle Subtypes?mentioning
confidence: 99%
“…DLE occurs more frequently in women in their fourth and fifth decade of life [11]. Patients with DLE generally have a more benign disease course as compared to patients with other CLE subtypes, with only a reported 5-10% developing SLE throughout their disease course [28,29]. Studies have shown that patients with generalized DLE are more likely to progress to systemic disease, compared to patients with localized DLE [9,30].…”
Section: How Can We Differentiate the Cle Subtypes?mentioning
confidence: 99%
“…18 However, adults with DLE who develop SLE often have mild clinical disease with infrequent neurologic and renal involvement. 14,19,20 Wieczorek et al 11 found that most patients with DLE were given the diagnosis of SLE by meeting mucocutaneous and laboratory criteria without development of end-organ damage.…”
mentioning
confidence: 98%
“…[7][8][9][10] In adults, the frequency of progression of DLE to SLE is reported to range from 0% to 28%, with an interval between onset of DLE and SLE ranging from months to decades. [10][11][12][13][14] Lesions are further classified as localized (confined to the head and neck) or generalized (involving the entire body); this distinction may be clinically significant, as some studies in both adults and children have demonstrated a higher risk of SLE with generalized DLE. [15][16][17][18] Nephropathy, arthralgias, and elevated antinuclear antibody titers may also predict transformation to SLE in adults.…”
mentioning
confidence: 98%
“…Up to 28% of patients with DLE develop SLE (10), while 0.9-2.4% of patients with SLE develop HPS (11). We initially suspected that our case progressed from DLE to SLE developing HPS.…”
Section: Discussionmentioning
confidence: 99%